Dysregulated hematopoietic stem and progenitor cell activity promotes interleukin-23-driven chronic intestinal inflammation. - Griseri, T; McKenzie, B; Schiering, C; Powrie, F (2012)
In interleukin-23 (IL-23)-dependent colitis, there is excessive accumulation of short-lived neutrophils and inflammatory monocytes in the intestine. It is unknown whether this reflects changes in mature cell populations or whether the IL-23-driven colitogenic T cell program regulates upstream hematopoietic stem and progenitor cells (HSPC). Here we have shown dysregulation of hematopoiesis in colitis mediated by inflammatory cytokines. First, there was an interferon-gamma-dependent accumulation of proliferating hematopoietic stem cells in the bone marrow and spleen. Second, there was a strong skew toward granulocyte-monocyte progenitor (GMP) production at the expense of erythroid and lymphoid progenitors. Extramedullary hematopoiesis was also evident, and granulocyte macrophage-colony stimulating factor (GM-CSF) blockade reduced the accumulation of splenic and colonic GMPs, resulting in amelioration of colitis. Importantly, transfer of GMPs exacerbated colitis. These data identify HSPCs as a major target of the IL-23-driven inflammatory axis suggesting therapeutic strategies for the treatment of inflammatory bowel disease.